Cordel, letramento literário e verbo-visualidade : três conceitos, um autor, uma história, um folheto - Roza, Edleide Santos (2018)
This study, entitled: Cordel, literary literacy and verb-visuality: three concepts, an author, a history, a pamphlets, objectified to carry through the reading verb-appearance of the cordel pamphlets A mulher que se casou dezoito vezes…, of Valeriano Felix dos Santos, propitiating the literary literacy for pupils from the Eighth grade – Elementary Level – from Professor Luiz Antonio Barreto Basic School, tied to the Municipal Teaching Network, in Riachão do Dantas, in the State of Sergipe, native city of the mentioned author. Reasoned on the studies of Maranhão (1981), Terra (1981; 1983), Curran (1987), Abreu (1999), Bakhtin (1997; 2010), Roiphe (2011; 2013), Cosson (2014), among other authors, this work was structuralized around a didactic sequence that contains several activities and games that, for its performance, needed the simultaneous reading of the constitutive verbal and visual languages from the cordel pamphlets. The sequence was applied in the selected class and the students learned what cordel is, met another author from their land, read and analyzed his most significant work. They did the simultaneous both word and image for a more complete production of the senses present in the studied pamphlets, from the expectation of them to use this practice more effectively in their everyday life, when reading other texts constituted verb-visually, especially the cordéis. The obtained results were exposed in this report and the developed sequence was affixed to the pedagogical notebook – final product of this work.